Games for the to familiarize before to the initiation of the handball in the age school - Cordoves Peinado, R.; Mesa Sánchez, L.; Aguilera Ramírez, B.; Juárez López, A. J.; Larios Núñez, R.; Gutierrez Cruzata, D. (Journal of Human Sport & Exercise, 2026)
This study aimed to design and validate a system of games for familiarization with handball initiation in five-year-old preschool children from the Mella-Jayama district of Camagüey municipality. The research was structured in three phases: diagnosis, design, and practical validation. The diagnosis phase, conducted using an adapted TGMD-3 battery, assessed a population of 32 children (from a total of 58) and revealed significant deficits in object manipulation skills (catching and throwing) and their integration (0% success rate in precision and space adaptation indicators), despite adequate development of locomotor skills. This finding justified the need for a specific intervention. The design phase was based on the principles of play-based learning and the Teaching Games for Understanding (TGfU) model, resulting in a structured system of games focused on sensory-motor familiarization with the ball, basic technical actions, and simplified game situations. The validation phase, based on implementation by educators and perceived utility surveys (Likert scale 1-5), showed an exceptional consensus among practitioners. The system received median scores of 5/5 in clarity, age-appropriateness, children's enjoyment, and perceived contribution to motor development, and 4.5/5 in practical feasibility. Qualitative analysis from a focus group highlighted high levels of child motivation and observable progress in initially deficient skills. The study concludes that the proposed game system is a pedagogically sound, effective, and highly motivating tool that addresses specific psychomotor needs in preschoolers, providing a solid foundation for inclusive and enjoyable handball initiation through play. It represents a practical and validated resource for early childhood physical education specialists.